2021
DOI: 10.6018/sportk.461561
|View full text |Cite
|
Sign up to set email alerts
|

Relación entre la práctica de actividad física y el apoyo social percibido de los adolescentes de la provincia de Soria

Abstract: Existe cierta preocupación social por conocer los niveles de práctica de actividad física de los adolescentes, para poder llevar a cabo propuestas de mejora si fuera necesario. Este estudio fue diseñado con la finalidad de conocer esos niveles de los adolescentes de Soria y el apoyo social que perciben para su práctica, tanto de familiares como de amigos, en función del sexo del alumnado, e identificar el tipo de relación existente entre su práctica y la percepción del apoyo social. La muestra estuvo formada p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
1
0
0
Order By: Relevance
“…Users are therefore more likely to show reduced adherence to exercise without this support [ 70 , 71 ]. It should also be noted that there are differences in social support according to gender [ 72 ]; in one study, it was found that men received more support from family and friends than women [ 73 ], just as in this study, wherein a lack of social support can be observed as a barrier to physical activity. Women’s participation in physical activity was shown to be lower than the participation of men with disabilities [ 14 , 16 , 20 ]; these differences are also significant when it comes to the perception of barriers to physical activity, according to gender [ 14 ], between men and women.…”
Section: Discussionsupporting
confidence: 50%
“…Users are therefore more likely to show reduced adherence to exercise without this support [ 70 , 71 ]. It should also be noted that there are differences in social support according to gender [ 72 ]; in one study, it was found that men received more support from family and friends than women [ 73 ], just as in this study, wherein a lack of social support can be observed as a barrier to physical activity. Women’s participation in physical activity was shown to be lower than the participation of men with disabilities [ 14 , 16 , 20 ]; these differences are also significant when it comes to the perception of barriers to physical activity, according to gender [ 14 ], between men and women.…”
Section: Discussionsupporting
confidence: 50%